A study of familial Char syndrome involving the TFAP2B gene with a focus on facial shape characteristics. Issue 3 (July 2018) - Nyboe, Daniel; Kreiborg, Sven; Darvann, Tron; Dunø, Morten; Nissen, Kamilla R.; Hove, Hanne B.
Abstract : In this case study, we investigate a child presenting with patent ductus arteriosus, short philtrum, duck-bill lips, strabismus, a flat nasal bridge, a broad forehead, low-set ears, hypertelorism, up-slanting palpebral fissures, almond-shaped eyes, and hypodontia, all leading to the clinical diagnosis of Char syndrome. Genetic analysis showed heterozygosity for the novel variant c.851T>C, p. Leu284Ser in the TFAP2B gene. Family analysis suggested that at least 20 members, extending six generations back, were affected. All 10 members available for genetic testing were heterozygous for the novel pathogenic variant. Qualitative analysis of the facial dysmorphology in the proband and three of the affected family members using three-dimensional surface scanning showed that the major deviations were observed in the forehead/eyebrow, nose, upper lip, and chin regions with, for example, a flattened nose and reduced height of the upper lip and the face. Furthermore, it is suggested that Char syndrome is associated with disturbances of tooth formation and eruption.